Identities at odds: embedded and implicit language policing in the internationalized workplace - Hazel, Spencer (Taylor & Francis, 2015)
This study offers an interaction analytic account of how linguistic identities in internationalized workplaces in Denmark are indexed against members' institutional positions in particular interactional contexts. Where language policy may not be explicitly articulated between members, it is still embedded in how participants micro-manage their interactions and implicit in how members display orientations to deviance, in the case of encountering others in the workplace whose language repertoires or preferences do not meet with expectation pertaining to the institutional position they hold. The study uses recordings of naturally occurring interaction in different international workplace settings and argues for greater attention to be paid to the actual language-policy practices in international workplace settings, as an entry point into developing a more nuanced understanding of the practices through which professional identities are brought about, affirmed or contested, and the linguistic considerations that are implicated in this.